Stephen of Orléans-Tournai in France. The Lost Years 1145-1167 - Conklin, George Newton (Sacris erudiri, 2022)
This article addresses the obscure years from 1145-1167 in the life of the renowned canonist, abbot, and bishop Stephen of Orléans-Tournai. In the first part, it reconstructs where and when he was in these so-called lost years. It reconciles the given dates in several letters and proposes that he made two trips to Bologna instead of one where he studied canon law, composed his own legal Summa, and also taught canon law. It adduces that he witnessed the transformation of St Euverte (Orléans) from a house of secular to one of canons regulars, but that he himself delayed his own conversion to that life until he returned to his monastery from Italy. Given the dates of the letters, the two-trip theory supports a recent proposal that he taught in Bologna, which would not have been possible were there only a single trip. The second part of this article is intended to touch upon several facets of this active prelate’s life in and on behalf of the church so that, for example, his neglected sacramentology, the theory and practice of canon law, and his importance to the spiritual and educational life of twelfth-century France come into better relief.